Poetry on the plains: J.S. Penny and the environmental history of Fort Scott - Blake, Daron (Kansas State University, 2012)
This thesis recreates the relationship between humans and their physical environment in Fort Scott, Kansas between 1850 and 1920 and uses the poetry of J.S. Penny, a contemporary amateur poet living and writing in Fort Scott, as an essential primary resource. Settlers came to this area in southeastern Kansas in the 19th century for its timber-lined streams, high precipitation, and rich soil. The Missouri River, Fort Scott, and Gulf Railroad was extended through Fort Scott in December of 1869. The arrival of the railroad transformed the town. The natural resources which had been a mark of identity for the people of Fort Scott became commodities to be sold in national markets. Manufacturing and industry boomed, but population would eventually plateau in the early 20th century, creating a small industrial city that had maintained a strongly rural sense of community. Penny’s poetry provides a personal, emotional response to the rapid changes to the landscape around him. Some of his poems on the local landscape directly note specific changes in the local ecology, while some demonstrate Penny’s religious connection the natural world—a common perspective during his time. Other pieces show us Penny’s observations of how his neighbors reacted to the weather and environment in Fort Scott. Penny, like many Americans in the early 20th century, saw the history of his home as one of agrarian development and westward expansion over an empty landscape; the Jeffersonian and Turnerian roots of his perspective are evident in his poetry. With Penny’s poetry, we can create a more complete environmental history of Fort Scott by understanding how Fort Scott residents related to the land around them.
Keywords: Kansas; Fort Scott; J.S. Penny; Kansas poetry; Environmental history; Midwestern poetry; Environmental Studies (0477); History (0578); Literature (0401)